PROBLEMS OF WIRES MIGRATION OF INLAYS OF METAL CORD OF COMPACT STRUCTURES - A. V. Vedeneyev; Yu. V. Feoktistov; B. A. Biryukov; V. I. Gritsayenko (Литьë и металлургия, 2012)
It is shown that at manufacture of metal cord of compact constructions there is a possibility to control by various processing methods the inclination of metal cord layers to migration.